Adjuvant effect of herbal medicine on transarterial chemoembolization in patients with hepatocellular carcinoma: A systematic review and meta-analysis - Oh, Hyeon-Muk; Kim, Eun-Ji; Bae, Hye-Ri; Cho, Jung-Hyo; Son, Chang-Gue; Lee, Nam-Hun (Frontiers in Oncology, 2023)
Objectives: Primary hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related deaths, especially in Asian countries. As a practical treatment option, transarterial chemoembolization (TACE) has been well applied; however, its limited efficacy remains challenging. This study analyzed the adjuvant effects of herbal medicine on TACE to determine whether it improves clinical outcomes in patients with HCC. Methods: A systematic review and meta-analysis was performed to compare the adjuvant effects of herbal medicine on TACE versus TACE therapy alone. We searched the literature from eight databases since January 2011. Results: Twenty-five studies involving 2,623 participants were selected. The adjuvant therapy of herbal medicine on TACE improved the overall survival at 0.5 years (OR = 1.70; 95% CI 1.21-2.38), 1 year (OR = 2.01; 95% CI 1.65-2.46), 2 years (OR = 1.83; 95% CI 1.20-2.80), and 3 years (OR = 1.90; 95% CI 1.25-2.91). The combination therapy also increased the tumor response rate (OR = 1.84; 95% CI 1.40-2.42). Conclusions: Despite the unsatisfactory quality of the included studies, the adjuvant therapy of herbal medicine on TACE may provide survival benefits to patients with HCC.